SARS-CoV-2 infection and male fertility problems - Ika Inda Bani; Zulkarnain Zulkarnain; Gholib Gholib; Dedy Syahrizal; Fauzul Husna; Winda Yulia; Mulkan Azhari (Trends in Infection and Global Health, 2022)
In 2019, the coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome corona virus 2 (SARS-CoV-2), has killed more than 6.6 millions of people around the world as of end of 2022. The long-term impact of COVID-19 is persisted, including its impact on male reproduction. SARS-CoV-2 enters into host cells using the angiotensin-converting enzyme 2 (ACE2) and transmembrane serine protease 2 (TMPRSS2) receptors. Both of these receptors are expressed more in men, and therefore men are more susceptible to SARS-CoV-2. COVID-19 potentially cause infertility by damaging testicular tissues and interfering with the process of spermatogenesis. A decrease in serum levels of testosterone, follicle-stimulating hormone (FSH) and luteinizing hormone (LH) as well as a decrease in sperm quality in men with COVID-19 compared to healthy men of the same age has been reported in several studies. Utilizing existing research data, this study aims to explore in detail of how SARS-CoV-2 tends to affect male fertility.